Comparison of fetal growth assessment by conventional method and by using intergrowth 21st chart for detecting small for gestation fetuses - Millo, Suka; Puri, Manju; Singh, Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Low birthweight is a major contributor to neonatal morbidity and mortality. Conventionally, fetal growth is assessed by clinical palpation of fundal height (FH), which could have significant inter-observer variation. Routine ultrasound, though a reliable tool, is not cost-effective for low-resource settings. Symphysio-FH (SFH) measurement plotted on customized charts is another tool for monitoring fetal growth. The study aims to compare SFH measurement charted on intergrowth 21st international symphysis FH (SFH) graph charts with FH palpation as a method for detecting small for gestation age (SGA) fetuses. Methods: This prospective observational analytic study was conducted on 500 pregnant women. SGA was suspected in case of a lag of ≥3 weeks in FH palpation or SFH plotted on intergrowth 21st charts falling below 10th centile. Birthweight of new-born was plotted on intergrowth 21st estimated foetal weight chart. Birthweight below 10th centile was classified as SGA. Results: Out of 500 pregnancies, 13.2% new-borns were SGA. SFH measurement showed 99.5% specificity and 83.3% sensitivity compared to 98.6% specificity and 69.9% sensitivity by FH measurement for SGA detection. SFH measurement also had higher true positive (83.3% vs 69.6%), and true negative (97.5% vs 95.5%) value, and missed lesser cases (2.4% vs 4.5%) compared to FH palpation. Conclusions: The study found SFH plotted on 21st intergrowth chart to be more sensitive and specific in detecting SGA new-borns compared to conventional FH palpation.